PROPERTY TAX AS A TOOL FOR FINANCIAL REGULATION OF PUBLIC WELFARE (World of finance, 2020)
Introduction. With the approval of the concept of inclusive development, the demand for scientific research aimed at finding ways to implement it in financial practice is growing, which will have a positive impact on indicators of public welfare. In this context, an important task is to ensure the integration of the principles of inclusive development into the practice of property taxation, which will ensure an increase in its efficiency and fairness.The purpose is to reveal the social aspects of property tax, including assessing the compliance of the tax collection mechanism with the principles of fairness and inclusiveness of taxation, as well as the impact of property tax on the welfare of payers, taking into account their differentiation by the level of personal income.Methods. In the article, when studying the social aspects of levying property tax, general scientific and special methods are applied, namely, generalization, comparison, grouping, tabular analysis. Results. It has been substantiated that property tax has a varied effect on public welfare, acting as a tool for ensuring the redistribution of wealth between various social groups, attracting shadow incomes to taxation, withdrawn from it thanks to schemes to minimize tax liabilities, an instrument for curbing speculation in the housing market, as well as an important source of budget revenues, which are largely directed to social goals. It has been proven that in domestic practice, real estate tax has a pronounced regressiveness and discriminatory nature in relation to payers with lower incomes. Real estate tax rates are too low, which is more beneficial for wealthy citizens and leads to losses in local budget revenues. This made it possible to argue the advisability of switching to a cost approach to determining the tax base, but only available within an appropriate institutional environment.Perspectives. Further scientific research should be directed towards finding the optimal approach to establishing the base of real estate, as well as ensuring the inclusiveness of taxation, when opportunities for tax evasion will be minimized.